Acute exanthemas: a prospective study of 98 adult patients with an emphasis on cytokinic and metagenomic investigation. (1st February 2020) - Deschamps, O.; Ortonne, N.; Hüe, S.; Rodriguez, C.; Deschodt, C.; Hirsch, G.; Colin, A.; Grégoire, L.; Delfau‐Larue, M.‐H.; Chosidow, O.; Wolkenstein, P.; Ingen‐Housz‐Oro, S.
Summary: Background: Acute exanthemas (AEs) are frequently seen; they can be caused by drugs or viruses but often the cause is unknown. Objectives: To describe the clinical, virological and histological aspects of AEs and explore their cytokinic and metagenomic profiles. Methods: This prospective study examined 98 patients with AE, from February to July 2014. Clinical data were recorded in a standardized chart. Virological investigation and skin biopsies were performed. In addition, blood and skin samples were analysed for cytokines and then by a shotgun metagenomic approach. We identified five groups of patients: those with maculopapular exanthemas (MPEs) that were virally induced (group 1); those with drug‐induced MPEs (group 2), those with MPEs that were both viral and drug induced (group 3), those with idiopathic MPEs (group 4) and those with pityriasis rosea (group 5). Results: A virus was identified in 29 cases (human herpesvirus 6, 72%). Cytokinic analysis of the skin ( n = 23 MPEs) showed higher levels of interferon‐γ and interleukin‐1 receptor‐α in viral MPEs, higher interleukin‐33 levels in idiopathic MPEs, and higher macrophage inflammatory protein 1α levels in drug‐induced MPEs. By metagenomics analysis ( n = 10 MPEs), viruses identified with routine practice methods were not found in group 1 ( n = 4 MPEs). However, Enterovirus A was detected in two cases, especially in a group 1 patient for whom metagenomic analysis rectified the diagnosis of the culprit agent. Conclusions: Human herpesvirus 6 was the virus most frequently identified, and histology did not discriminate MPEs. In addition, the level of interleukin‐33 seen in idiopathic MPEs suggests that an environmental factor may be the trigger for these. The results bring into question the utility of routine polymerase chain reaction analysis and viral serology for determining cause in AE. What's already known about this topic? Acute exanthemas, especially maculopapular exanthemas, are a frequent reason for patients consulting emergency and dermatology departments. It is difficult to evaluate the aetiology of acute exanthema based on the clinical aspects. Few data are available on the investigations needed in routine practice, and no prospective series have been published. What does this study add? Our study provides a global and prospective description of acute exanthemas. Cytokine analysis could help to investigate the pathophysiology of idiopathic eruptions. Metagenomic analysis provides new insights about the value of routine practice virological investigations. We show for the first time the feasibility of metagenomics analysis in the skin, which results question the interest of routine PCR and viral sérologies for the exploration of such acute exanthemas.